2019
DOI: 10.1111/jocn.15004
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in specialised palliative care: Healthcare professionals' and their perspectives on video consultations—A qualitative study

Abstract: Aims and objectives To explore the advantages and disadvantages of using video consultations, as experienced by specialised palliative care healthcare professionals, who are involved in palliative care at home. Background One challenge in the work of specialised palliative care teams is the substantial resources used in terms of time and transport to and from the patient's home. Video consultations may be a solution for real‐time specialised palliative home care. Designs Hermeneutic, postphenomenology. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 17 publications
3
71
0
2
Order By: Relevance
“…Previously, the use of telemedicine in palliative care showed improvements in symptom management, comfort with care, and patient and family satisfaction ( 35 ). It also facilitated cooperation between the community nurses and the specialized palliative care team nurse ( 36 ). Still, potential barriers were technology-related complications in the elderly and frail population ( 35 ) and private issues regarding the illness, with family members present ( 36 ).…”
Section: Palliative Care During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the use of telemedicine in palliative care showed improvements in symptom management, comfort with care, and patient and family satisfaction ( 35 ). It also facilitated cooperation between the community nurses and the specialized palliative care team nurse ( 36 ). Still, potential barriers were technology-related complications in the elderly and frail population ( 35 ) and private issues regarding the illness, with family members present ( 36 ).…”
Section: Palliative Care During Covid-19mentioning
confidence: 99%
“…It also facilitated cooperation between the community nurses and the specialized palliative care team nurse ( 36 ). Still, potential barriers were technology-related complications in the elderly and frail population ( 35 ) and private issues regarding the illness, with family members present ( 36 ). Moreover, patients, as well as physicians, did not always feel comfortable with non-face-to-face physician care.…”
Section: Palliative Care During Covid-19mentioning
confidence: 99%
“…A limited number of studies have explored technology acceptance within palliative care. Some of the evaluated technologies allowed for monitoring and assessing symptoms [7,18,20,21], while others for video consultations, exclusively [22]. Among these studies, factors supporting acceptance included demonstrated evidence that technology could enhance patient outcomes/experiences [20,21] and could act as an adjunct to in-person care [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, factors supporting acceptance included demonstrated evidence that technology could enhance patient outcomes/experiences [20,21] and could act as an adjunct to in-person care [7,18]. Technologies that were tailored to meet the specific needs of different palliative care settings [22] also supported provider acceptance. Conversely, perceived lack of clinical relevance (of aspects of the technology) [20], lack of digital infrastructure to support technology [7,18], and privacy concerns [22] were notable barriers to technology acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation